2017
DOI: 10.1177/0897190017696953
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacist Intervention on Selection and Timing of Appropriate Antimicrobial Therapy in Septic Shock

Abstract: Pharmacist assessment of patients in septic shock offers the opportunity to improve SSAT. Systems designed to use a pharmacist responder for the care of patients with septic shock maximize the selection of antimicrobials, facilitate rapid administration, and improve surrogate outcomes for mortality in septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 20 publications
(42 reference statements)
1
25
0
1
Order By: Relevance
“…và cộng sự (2018), nghiên cứu đánh giá can thiệp dược sĩ trên tỷ lệ bệnh nhân được chỉ định kháng sinh kinh nghiệm hợp lý với kháng sinh đồ (định nghĩa là chọn kháng sinh kinh nghiệm có phổ bao phủ vi khuẩn phân lập được) tại Hoa Kỳ, so sánh trước và sau khi có sự can thiệp. Sự can thiệp của dược sĩ đã tăng tỷ lệ bệnh nhân được chỉ định kháng sinh hợp lý theo kháng sinh đồ từ 66% lên 80% (p= 0,04) [6].…”
Section: Bàn Luậnunclassified
“…và cộng sự (2018), nghiên cứu đánh giá can thiệp dược sĩ trên tỷ lệ bệnh nhân được chỉ định kháng sinh kinh nghiệm hợp lý với kháng sinh đồ (định nghĩa là chọn kháng sinh kinh nghiệm có phổ bao phủ vi khuẩn phân lập được) tại Hoa Kỳ, so sánh trước và sau khi có sự can thiệp. Sự can thiệp của dược sĩ đã tăng tỷ lệ bệnh nhân được chỉ định kháng sinh hợp lý theo kháng sinh đồ từ 66% lên 80% (p= 0,04) [6].…”
Section: Bàn Luậnunclassified
“…The spectrum of the antimicrobial agents can be narrowed as culture results become available or the patient presentation changes. Input from clinical pharmacists in the ED can assist in optimizing the initial antimicrobial choice and has been shown to decrease time to antibiotic administration, improve antibiotic stewardship, and improve patient outcomes [9][10][11][12].…”
Section: Guidelines For the Management Of Sepsis Spectrum Disordersmentioning
confidence: 99%
“…Multiple studies have been published describing the benefits of having a dedicated ICU pharmacist . These include a reduction in adverse drug events (ADEs), improved antibiotic use, decreased rates of hospital‐acquired infections, decreased length of stay and a reduction in both ICU and hospital mortality . Studies have also shown an economic benefit of ICU pharmacists mostly in reducing preventable ADEs .…”
Section: Introductionmentioning
confidence: 99%
“…[3,[5][6][7][8][9][10] These include a reduction in adverse drug events (ADEs), improved antibiotic use, decreased rates of hospital-acquired infections, decreased length of stay and a reduction in both ICU and hospital mortality. [3,[5][6][7][8]10] Studies have also shown an economic benefit of ICU pharmacists mostly in reducing preventable ADEs. [7,9] Despite the benefits of ICU pharmacists, not all hospitals have adopted this model.…”
Section: Introductionmentioning
confidence: 99%